Evaluation of Melamine Content in Infant Formula Collected from Different Areas of Tehran, Iran, Using Enzyme-Linked Immunosorbent Assay Method - Hamidreza Kazemeini; Asghar Azizian; Katayoun Ahmadi (تحقیقات نظام سلامت, 2022)
Background: Detection of adulteration of the melamine addition to food products, which is done to increase the nitrogen content, is essential because of its risks to consumer health. The aim of this study was to investigate the amount of melamine in milk powder consumed by infants collected from different parts of Tehran, Iran, using enzyme-linked immunosorbent assay (ELISA) method in 2021. Methods: In this study, 22 samples of infant formula consumed with different brands of the best-selling ones were collected in 22 districts of Tehran, and using ELISA-based diagnostic kit, melamine was searched, diagnosed, and its amount was determined and then compared with the standard limit. Findings: Based on the results, in none of the samples of infant formula, values higher than the detection limit of the kit were observed. Conclusion: According to the results of this study, it was found that melamine was not cheated in infant formula in Tehran in 2021 and in this regard, there is no danger to the consumer (infants).